Cement-based composite material and preparation method thereof

By using microfluidic chips in the cement base material to prepare and self -assembled heat -conducting enhanced phase transformer micro -capsules, the existing technologies have a poor leakage, volatile, and thermal conductivity in the existing technology in the cement base material The problem has achieved efficient thermal regulation performance and good energy storage effects.

CN119330672AActive Publication Date: 2025-01-21NANJING TECH UNIV

Patent Information

Application Number
CN202411610216.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing phase change materials have problems such as leakage, volatility, poor thermal conductivity and uneven microcapsule particle size in cement-based materials, resulting in poor energy storage effect and limited application.

Method used

Make a micro -control chip to prepare a uniform and controllable thermal conductivity to enhance the phase -changing energy storage micro -capsule, and control the wall thickness of the microcapsule through the layers of self -assembly method. Finally, add it to the cement slurry and achieve it in the cement base material Uniformly scattered.

Benefits of technology

The encapsulation rate, monodispersity and thermal conductivity of the microcapsules are improved, the thickness of the wall material is controllable, the outer wall strength of the microcapsules is enhanced, leakage of phase change materials is avoided, and the thermal regulation performance of cement-based composite materials is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330672A_ABST
    Figure CN119330672A_ABST
Patent Text Reader

Abstract

The invention provides a cement-based composite material and a preparation method thereof, and belongs to the technical field of composite material preparation. The preparation method comprises the following steps: step 1, preparing a heat-conducting reinforced phase change energy storage microcapsule with uniform and controllable particle size; step 2, preparing a heat-conducting reinforced phase change energy storage microcapsule with controllable wall thickness; and step 3, preparing the phase change energy storage cement-based composite material test piece. Phase change energy storage microcapsules with uniform and controllable particle sizes and enhanced heat conduction are prepared through a micro-fluidic chip, then the wall thickness of the microcapsules is controlled through a layer-by-layer self-assembly method, finally, the wall-thickness-controllable heat conduction enhanced phase change energy storage microcapsules are added into cement paste, the microcapsules are dispersed in the cement paste, and the phase change energy storage microcapsules are prepared. Therefore, the phase-change energy-storage cement-based composite material with good thermal regulation capability is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite material preparation, in particular to a cement-based composite material and a preparation method thereof, and more particularly to a cement-based composite material prepared based on thermally conductive enhanced phase-change energy storage microcapsules with controllable wall thickness and a preparation method thereof. Background Art

[0002] As a new energy-saving technology, thermal energy storage technology plays an increasingly important role in saving energy and protecting the environment. It can be used to recover thermal energy, directly or indirectly reduce the corresponding natural resource consumption, reduce carbon emissions and protect the environment. Phase change energy storage, as a type of thermal energy storage technology, stores or releases energy through the principle that the material undergoes phase change while the temperature remains basically unchanged. It has the characteristics of high energy storage density and small temperature change of the material during the phase change process. In order to prevent the phase change material from directly contacting the cement-based material and affecting the performance of the cement-based material, the phase change material needs to be microencapsulated. However, there are still certain problems with the existing cement-based materials prepared with phase change material microcapsules, mainly as follows: the existing phase change materials are mainly solid-liquid organic phase change materials, which are prone to leakage and volatilization, causing the phase change materials to fail and shortening their service life; the existing phase change materials will reduce the overall thermal conductivity of the prepared cement-based structure, and the decrease in thermal conductivity will prolong the phase change reaction time of the phase change microcapsules, thereby affecting the energy storage effect; the existing phase change materials have poor thermal conductivity, and the phase change energy storage microcapsules prepared by commonly used in-situ polymerization, emulsion polymerization and other methods have uneven particle sizes, resulting in uneven dispersion in cement-based materials, affecting the energy storage efficiency, thereby limiting their application. Summary of the invention

[0003] In view of this, in order to solve the above-mentioned shortcomings of the existing phase change materials, on the one hand, the present invention provides a method for preparing a cement-based composite material, wherein phase change energy storage microcapsules with uniform and controllable particle size and enhanced thermal conductivity are prepared by a microfluidic chip, and then the wall thickness of the microcapsules is controlled by a layer-by-layer self-assembly method, and finally, the thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness are added to the cement slurry, and the microcapsules are dispersed in the cement slurry, thereby preparing a phase change energy storage cement-based composite material with good thermal regulation ability.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing a cement-based composite material comprises the following steps:

[0006] Step 1: Preparation of thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size

[0007] The phase change energy storage material in a molten state is mixed evenly with the heat conductive material to form an inner phase solution; the sodium alginate aqueous solution is mixed evenly with the surfactant to form an outer phase solution;

[0008] The inner phase solution and the outer phase solution are injected into the microfluidic chip to form water-in-oil microdroplets at the outlet of the microfluidic chip, and the microdroplets are poured into the receiving liquid with the assistance of gravity, and finally the thermal conductivity enhanced phase change energy storage microcapsules with uniform and controllable particle size are formed;

[0009] Step 2: Preparation of thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness

[0010] The thermally conductive enhanced phase-change energy storage microcapsules with uniform and controllable particle size prepared in step 1 are self-assembled layer by layer to obtain thermally conductive enhanced phase-change energy storage microcapsules with controllable wall thickness;

[0011] Step 3: Preparation of phase change energy storage cement-based composite material specimens

[0012] The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness obtained in step 2 are mixed with cement slurry, shaken multiple times, and solidified to obtain a phase change energy storage cement-based composite material specimen.

[0013] Preferably, in step 1, the preparation method of the inner phase solution is: adding the thermal conductive material directly into the phase change energy storage material in a molten state at a temperature of 50 to 70° C. and stirring, continuously stirring for 1 to 2 hours, and performing ultrasonic oscillation for 1 to 3 hours;

[0014] Preferably, the phase change energy storage material is a paraffin phase change material;

[0015] Preferably, the paraffin phase change material includes at least one of n-tetradecane, n-hexadecane, n-octadecane and n-eicosane;

[0016] Preferably, the thermally conductive material is a carbon-based material, and the carbon-based material is preferably at least one of graphite, graphene, graphene oxide, carbon nanotubes and carbon quantum dots;

[0017] Preferably, the concentration of the thermally conductive material in the inner phase solution is 0.1-0.5 wt %.

[0018] Preferably, in step 1, the preparation method of the external phase solution is: mixing water, sodium alginate and a surfactant at a temperature of 50 to 70° C., and stirring at a speed of 800 to 1000 r / min for 40 to 60 min;

[0019] Preferably, the surfactant is at least one of polysorbate 80, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl pyrrolidone;

[0020] Preferably, the concentration of sodium alginate in the external phase solution is 3-5 wt %; the concentration of surfactant in the external phase solution is 0.5-1 wt %.

[0021] Preferably, in step 1, the inner phase solution and the outer phase solution are injected into the microfluidic chip through a syringe pump, and the flow rate ratio of the inner phase solution to the outer phase solution is controlled;

[0022] Preferably, the flow rate ratio of the inner phase solution to the outer phase solution is 1 / 4-1 / 2;

[0023] Preferably, the receiving liquid is a CaCl2 solution with a mass fraction of 2 to 5 wt%;

[0024] Preferably, the microfluidic chip is suspended vertically along the outlet direction;

[0025] Preferably, the distance between the outlet end of the microfluidic chip and the liquid surface of the receiving liquid is 4 to 5 cm;

[0026] Preferably, the inner diameter of the inner glass capillary of the microfluidic chip is 100 to 500 μm, and the outer diameter is 500 to 900 μm;

[0027] Preferably, the inner diameter of the outer glass capillary of the microfluidic chip is 800-1200 μm, and the outer diameter is 1500-3000 μm.

[0028] Preferably, in step 2, the layer-by-layer self-assembly is to soak the thermal conductivity enhanced phase change energy storage microcapsules with uniform and controllable particle size prepared in step 1 in a sodium alginate solution, and then wash them with ethanol to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules; then, soak the pretreated thermal conductivity enhanced phase change energy storage microcapsules in a CaCl2 solution, take them out and wash them with ethanol to obtain a cycle treatment;

[0029] According to the above cycle, a thermally conductive enhanced phase change energy storage microcapsule with controllable wall thickness is obtained;

[0030] Preferably, the layer-by-layer self-assembly is to soak the thermal conductivity enhanced phase change energy storage microcapsules with uniform and controllable particle size prepared in step 1 in a sodium alginate solution with a mass fraction of 3-5wt% for 5-10 minutes, and then wash them with ethanol for 3-5 times to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules; then, soak the pretreated thermal conductivity enhanced phase change energy storage microcapsules in a CaCl2 solution with a mass fraction of 2-5wt% for 5-10 minutes, take them out and wash them with ethanol for 3-5 times to obtain a cyclically treated thermal conductivity enhanced phase change energy storage microcapsules;

[0031] According to the above cycle, thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are obtained.

[0032] Preferably, in step 2, the particle size of the prepared thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness is controllable in the range of 1500 to 3500 μm, and the wall thickness is controllable in the range of 100 to 1000 μm.

[0033] Preferably, step three is specifically:

[0034] The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness obtained in step 2 are placed in a 40-60° C. oven and dried for 24-48 hours. The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness are then mixed, stirred, and cured with cement slurry to obtain a phase change energy storage cement-based composite material specimen.

[0035] Preferably, in step three, the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are added in multiple times. Preferably, first, 1 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are added, and then 1 / 4 of the mold height of cement and water formed by cement slurry is added, and oscillated for 20 to 30 seconds, and then 3 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness and 1 / 2 of the mold height of cement slurry are added in turn, and oscillated for 20 to 30 seconds, and finally the remaining cement slurry is added to the mold.

[0036] In another aspect, the present invention provides a cement-based composite material, which is prepared by the above-mentioned method for preparing the cement-based composite material.

[0037] Preferably, the composition comprises, by weight: 100 to 200 parts of cement, 45 to 90 parts of water, and 10 to 15 parts of thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness prepared by the present invention have high encapsulation rate, good monodispersity, uniform and controllable size, good thermal conductivity, and controllable wall material thickness, which improves the strength of the outer wall of the microcapsule to prevent the microcapsule from rupturing in cement and causing leakage of the phase change material, and avoid direct contact between the phase change material and the cement-based material, which leads to a decrease in the performance of the cement-based material.

[0040] The particle size is controlled by the flow rate ratio, and the flow rate ratio in the present invention is limited to 1 / 4-1 / 2. The larger the flow rate ratio, the larger the particle size, and vice versa. The uniformity of particle size is controlled by the flow rate. As long as the flow rate is constant, the microcapsules produced are uniform in size.

[0041] The present invention improves thermal conductivity by adding thermal conductive material, improves the dispersibility of the thermal conductive material by multiple layered oscillations, ensures that the thermal conductive material is evenly dispersed, and makes the thermal conductivity uniform.

[0042] After the wall material is thickened, it will be dehydrated and dried. After the wall material is dried, the overall density of the wall material becomes larger, and the effect on the thermal conductivity is minimal. The increase in wall thickness increases the strength of the outer wall of the microcapsule, and the effect on its thermal conductivity is minimal.

[0043] (2) The phase change energy storage cement-based composite material specimen prepared by the present invention has good thermal regulation performance and can fully utilize the heat absorption and release capacity of the phase change material, thereby achieving the purpose of reducing indoor temperature fluctuations and controlling indoor temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic diagram of the structure of a microfluidic chip for preparing phase-change microcapsules according to the present invention;

[0045] Figure 2 A device for preparing thermally conductive enhanced phase change microcapsules;

[0046] Figure 3 It is a thermally conductive enhanced phase change energy storage microcapsule with controllable wall thickness;

[0047] Figure 4 A phase change energy storage cement-based composite material specimen prepared by the present invention;

[0048] In the figure, 1. metal sleeve; 2. inner phase glass capillary; 3. outer phase glass capillary; 4. conical transition tube; 5. glass slide; 6. outer phase solution and syringe connected to injection pump; 7. inner phase solution and syringe connected to injection pump; 8. polytetrafluoroethylene capillary tube; 9. culture dish; 10. receiving liquid; 11. heating source; 12. core material; 13. self-assembled wall material; 14. thermal conductive material; 15. cement-based material; 16. thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness. DETAILED DESCRIPTION

[0049] The method for preparing the cement-based composite material provided by the present invention comprises the following steps:

[0050] Step 1: Preparation of thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size

[0051] The phase change energy storage material in a molten state is mixed evenly with the heat conductive material 14 to form an inner phase solution; the sodium alginate aqueous solution is mixed evenly with the surfactant to form an outer phase solution;

[0052] The inner phase solution and the outer phase solution are injected into the microfluidic chip to form water-in-oil microdroplets at the outlet of the microfluidic chip, and the microdroplets are poured into the receiving liquid 10 with the assistance of gravity, and finally form thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size;

[0053] The details are as follows:

[0054] (1) The preparation method of the inner phase solution is as follows: preferably, by weight, 99.5 to 99.9 parts of molten phase change energy storage material and 0.1 to 0.5 parts of thermal conductive material 14 are poured into a glass beaker, and the mixed solution is placed on a magnetic stirrer at a temperature of preferably 50 to 70° C., and stirred at a speed of 800 to 1000 r / min for 1 to 2 hours, and then preferably sealed and placed in an ultrasonic oscillator for ultrasonic oscillation for 1 to 3 hours, with the temperature during oscillation maintained at 50 to 70° C., and stirred every 30 minutes to obtain the inner phase solution.

[0055] (2) The preparation method of the external phase solution is as follows: preferably, by weight, 3 to 5 parts of sodium alginate, 0.5 to 1 part of a surfactant, and 96.5 to 94 parts of water are poured into a glass beaker, and the mixed solution is placed on a magnetic stirrer, preferably at 50 to 70° C. and a speed of 800 to 1000 r / min, and stirred for 40 to 60 minutes to obtain the external phase solution.

[0056] (3) Preparation of receiving liquid 10: Based on weight, preferably 2 to 5 parts of anhydrous calcium chloride and 95 to 98 parts of water are mixed and stirred to prepare a CaCl2 solution with a mass fraction of preferably 2 to 5 wt%.

[0057] (4) The microfluidic chip is suspended vertically in the outlet direction, and the distance between the outlet end and the liquid surface of the receiving liquid 10 is preferably 4 to 5 cm.

[0058] (5) Use a syringe pump to inject the inner phase and outer phase solutions into the polytetrafluoroethylene capillary tube 8. The syringe pump controls the flow rate ratio of the inner phase to the outer phase to be preferably 1 / 4 to 1 / 2. Phase change energy storage microcapsules with different particle sizes can be obtained by different flow rate ratios, thereby achieving the purpose of controlling the particle size. Thermally conductive enhanced phase change energy storage microcapsules are formed at the outlet of the microfluidic chip, and the microdroplets are dripped into the receiving liquid 10 with the assistance of gravity, finally forming thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size.

[0059] Among them, the phase change energy storage material is preferably a paraffin phase change material; the paraffin phase change material preferably includes at least one of n-tetradecane, n-hexadecane, n-octadecane and n-eicosane; the thermal conductive material 14 is preferably a carbon-based material, and the carbon-based material is preferably at least one of graphite, graphene, graphene oxide, carbon nanotubes and carbon quantum dots; in the present invention, the concentration of the thermal conductive material 14 in the inner phase solution is preferably 0.1-0.5wt%, wherein the thermal conductive material 14 can improve the thermal conductivity of the phase change microcapsules.

[0060] In the present invention, the surfactant is at least one of polysorbate 80, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl pyrrolidone.

[0061] In the present invention, the concentration of sodium alginate in the external phase solution is 3-5 wt %; the concentration of surfactant in the external phase solution is 0.5-1 wt %.

[0062] The inner phase solution and the outer phase solution are injected into the microfluidic chip through a syringe pump, and the flow rate ratio of the inner phase solution to the outer phase solution is controlled; the flow rate ratio of the inner phase solution to the outer phase solution is 1 / 4-1 / 2.

[0063] like Figure 1-2 As shown, the present invention provides an embodiment of a microfluidic chip, the microfluidic chip comprising:

[0064] The glass slide 5 is provided with an inner phase glass capillary 2 and an outer phase glass capillary 3 at its upper and lower ends respectively. The outer phase glass capillary 3 is sleeved outside the inner phase glass tube, and its length is 1 / 3 to 1 / 2 of the inner phase glass capillary 2, and one end is flush with the inner phase glass capillary 2. A conical transition tube 4 is buckled on the non-flush end, and the three are fixed on the glass slide 5 with a sealant. A capillary metal sleeve 1 is sleeved on the non-flush end of the inner phase glass capillary 2 and the outer phase glass capillary 3, so as to form protection for the end of the inner phase glass capillary 2.

[0065] The inlet end of the inner phase glass capillary 2 and the inlet end of the tapered transition tube 4 are connected to the outer phase solution and the syringe is connected to the injection pump 6 and the inner phase solution and the syringe is connected to the injection pump 7 respectively through a polytetrafluoroethylene capillary.

[0066] The outer glass capillary 3 has an inner diameter of 800-1200 μm and an outer diameter of 1600-3000 μm; an inner diameter of 100-500 μm and an outer diameter of 500-900 μm; the outer glass capillary 3 and the inner glass capillary 2 are concentrically fitted.

[0067] The receiving liquid 10 is contained in a culture dish 9 , and the microcapsules formed at the outlet of the microfluidic chip are dripped into the receiving liquid 10 .

[0068] A heating source 11 may also be provided in the microfluidic chip to prevent the influence of temperature changes on the phase change energy storage material.

[0069] Step 2: Preparation of thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness 16

[0070] The thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size prepared in step 1 are self-assembled layer by layer to obtain thermally conductive enhanced phase change energy storage microcapsules 16 with controllable wall thickness;

[0071] The layer-by-layer self-assembly is to soak the thermal conductivity enhanced phase change energy storage microcapsules with uniform and controllable particle size prepared in step 1 in a sodium alginate solution, and then wash them with ethanol to obtain pre-treated thermal conductivity enhanced phase change energy storage microcapsules; then, soak the pre-treated thermal conductivity enhanced phase change energy storage microcapsules in a CaCl2 solution, take them out and wash them with ethanol to obtain a cycle treatment;

[0072] According to the above cycle, the self-assembly cycle can gradually increase the wall thickness, so that the shell strength of the microcapsule is gradually improved, and the microcapsule is prevented from rupturing and causing the internal phase change material to leak. According to the wall thickness requirement, the wall thickness can be controlled by the number of cycles to obtain the thermal conductivity enhanced phase change energy storage microcapsule 16;

[0073] The details are as follows:

[0074] (6) The prepared thermal conductivity enhanced phase change energy storage microcapsules are soaked in a sodium alginate solution with a mass fraction of 3 to 5wt% for 5 to 10 minutes, and then washed with ethanol for 3 to 5 times to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules. Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules are soaked in a CaCl2 solution with a mass fraction of 2 to 5wt% for 5 to 10 minutes, taken out and washed with ethanol for 3 to 5 times to obtain a cycle of thermal conductivity enhanced phase change energy storage microcapsules. According to the above cycle, thermal conductivity enhanced phase change energy storage microcapsules 16 with controllable wall thickness are obtained.

[0075] The particle size of the thermally conductive enhanced phase-change energy storage microcapsules 16 with controllable wall thickness prepared in step 2 is controllable in the range of 1500 to 3500 μm, and the wall thickness is controllable in the range of 100 to 1000 μm.

[0076] like Figure 3 As shown, the core material 12 of the thermally conductive enhanced phase-change energy storage microcapsule 16 with controllable wall thickness is wrapped with a self-assembled wall material 13 , and the self-assembled wall material 13 is wrapped with a thermally conductive material 14 .

[0077] Step 3: Preparation of phase change energy storage cement-based composite material specimens

[0078] The heat-conducting enhanced phase-change energy storage microcapsules 16 with controllable wall thickness obtained in step 2 are mixed with cement paste, shaken multiple times, and solidified to obtain a phase-change energy storage cement-based composite material specimen, as follows:

[0079] (7) The thermally conductive phase-change energy storage microcapsules 16 with controllable wall thickness were placed in an oven at 40 to 60°C and dried for 24 to 48 hours, and then phase-change energy storage cement-based composite material specimens were prepared. In order to prevent all microcapsules from floating on the surface of the cement paste after oscillation, the microcapsules were added to the mold in layers multiple times and oscillated multiple times.

[0080] The specific steps are:

[0081] First, add 1 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules 16 with controllable wall thickness, then add 1 / 4 of the cement slurry of the mold height, oscillate for 20 to 30 seconds, then add 3 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules 16 with controllable wall thickness and cement slurry of 1 / 2 of the mold height in turn, oscillate for 20 to 30 seconds, and finally add the remaining cement slurry to the mold to prepare a phase change energy storage cement-based composite material specimen. Multiple layered oscillations can improve the dispersion degree of the thermal conductivity enhanced phase change energy storage microcapsules 16 with controllable wall thickness in the cement, making it evenly dispersed.

[0082] like Figure 4 As shown, in the cement-based composite material specimen, the thermally conductive enhanced phase-change energy storage microcapsules 16 with controllable wall thickness are uniformly dispersed in the cement-based material 15, so that the cement-based composite material specimen has excellent thermal conductivity.

[0083] In another aspect, the present invention provides a cement-based composite material, which is prepared by the above-mentioned method for preparing the cement-based composite material.

[0084] In the present invention, the composition includes, by weight: 100-200 parts of cement, 45-90 parts of water, and 1610-15 parts of thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness.

[0085] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0086] Example 1

[0087] Step 1: Prepare thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size.

[0088] Use a 10ml syringe to draw 10ml of the external phase solution, the mass fraction of sodium alginate is 3%, the mass fraction of polysorbate 80 is 0.5%; use another syringe of the same specification to draw 10ml of the internal phase solution, the melting point of which is 24℃, the proportion of phase change paraffin is 99.9%, the mass fraction of graphene is 0.1%, and press Figure 2 Connect the device. Pour a 2% CaCl2 solution into a culture dish with a diameter of 120 mm and place it below the outlet of the microfluidic chip. Use a heating source to heat the inner phase solution through the channel so that it is always kept above 25°C. Set the external phase flow rate to 1500 μL / min; the internal phase flow rate to 375 μL / min, start the injection pump, form water-in-oil droplets at the outlet of the microfluidic chip, and solidify in the culture dish to form thermally conductive enhanced phase change energy storage microcapsules with a particle size of 2000-2400 μm.

[0089] Step 2: Prepare thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness.

[0090] The prepared thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 3% sodium alginate solution for 8 minutes, and then washed with ethanol 4 times to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules. Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 2wt% CaCl2 solution for 8 minutes, taken out and washed with ethanol 4 times to obtain a cycle of thermal conductivity enhanced phase change energy storage microcapsules. The above steps were cycled 3 times, and after being placed in a 50°C oven and dried for 36 hours, thermal conductivity enhanced phase change energy storage microcapsules with a wall thickness of 160-200μm were obtained.

[0091] Step 3: Prepare phase change energy storage cement-based composite material specimens.

[0092] The prepared thermally conductive enhanced phase change energy storage microcapsules were self-assembled layer by layer to obtain thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness, and then placed in a 50°C oven for drying for 36 hours, and then 100 parts of silicate cement, 45 parts of water, and 10 parts of thermally conductive enhanced phase change microcapsules with controllable wall thickness were mixed. The thermally conductive enhanced phase change microcapsules with controllable wall thickness were added to the mold in multiple batches and oscillated multiple times. The specific method is: first add 1 / 4 of the thermally conductive enhanced phase change microcapsules with controllable wall thickness, then add 1 / 4 of the cement slurry of the mold height, and then oscillate for 20 seconds, then add 3 / 4 of the thermally conductive enhanced phase change microcapsules with controllable wall thickness and 1 / 2 of the cement slurry of the mold height, oscillate for 20 seconds, and finally add the remaining cement slurry to the mold to prepare phase change energy storage cement-based composite material specimens.

[0093] Example 2

[0094] Step 1: Prepare thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size.

[0095] Use a 10ml syringe to draw 10ml of the external phase solution, the mass fraction of sodium alginate is 4%, the mass fraction of polysorbate 80 is 0.7%; use another syringe of the same specification to draw 10ml of the internal phase solution, the phase change material is n-octadecane with a proportion of 99.7%, the mass fraction of graphene is 0.3%, and press Figure 2 Connect the device. Pour a 4% CaCl2 solution into a culture dish with a diameter of 120 mm and place it below the outlet of the microfluidic chip. Use a heating source to heat the inner phase solution through the channel and keep it above 30°C. Set the external phase flow rate to 1500 μL / min; the internal phase flow rate to 400 μL / min, start the injection pump, form water-in-oil droplets at the outlet of the microfluidic chip, and solidify in the culture dish to form thermally conductive enhanced phase change energy storage microcapsules with a particle size of 2700-3000 μm.

[0096] Step 2: Prepare thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness.

[0097] The prepared thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 4% sodium alginate solution for 10 minutes, and then washed with ethanol 5 times to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules. Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 4wt% CaCl2 solution for 10 minutes, taken out and washed with ethanol 5 times to obtain a cycle of thermal conductivity enhanced phase change energy storage microcapsules. The above steps were repeated 4 times, and after being placed in a 50°C oven and dried for 36 hours, thermal conductivity enhanced phase change energy storage microcapsules with a wall thickness of 200-240μm were obtained.

[0098] Step 3: Prepare phase change energy storage cement-based composite material specimens.

[0099] After the wall thickness controllable thermal conductivity enhanced phase change energy storage microcapsules are placed in a 60°C oven and dried for 24 hours, 150 parts of silicate cement, 58 parts of water, and 13 parts of wall thickness controllable thermal conductivity enhanced phase change microcapsules are taken and mixed. The wall thickness controllable thermal conductivity enhanced phase change microcapsules are added to the mold in multiple batches and oscillated multiple times. The specific method is: first add 1 / 4 of the wall thickness controllable thermal conductivity enhanced phase change microcapsules, then add 1 / 4 of the mold height cement slurry, oscillate for 30 seconds, then add 3 / 4 of the wall thickness controllable thermal conductivity enhanced phase change microcapsules and 1 / 2 of the mold height cement slurry in turn, oscillate for 30 seconds, and finally add the remaining cement slurry to the mold to prepare a phase change energy storage cement-based composite material specimen.

[0100] Example 3

[0101] Step 1: Prepare thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size.

[0102] Use a 10ml syringe to draw 10ml of the external phase solution, the mass fraction of sodium alginate is 5%, the mass fraction of polysorbate 80 is 1%; use another syringe of the same specification to draw 10ml of the internal phase solution, the phase change material is n-octadecane with a proportion of 99.5%, the mass fraction of graphene is 0.5%, and press Figure 2 Connect the device. Pour a 5% CaCl2 solution into a culture dish with a diameter of 120 mm and place it below the outlet of the microfluidic chip. Use a heating source to heat the inner phase solution through the channel and keep it above 30°C. Set the external phase flow rate to 800 μL / min; the internal phase flow rate to 400 μL / min, start the injection pump, form water-in-oil droplets at the outlet of the microfluidic chip, and solidify in the culture dish to form thermally conductive enhanced phase change energy storage microcapsules with a particle size of 3000-3200 μm.

[0103] Step 2: Prepare thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness.

[0104] The prepared thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 5% sodium alginate solution for 10 minutes, and then washed with ethanol 5 times to obtain pretreated thermal conductivity enhanced phase change energy storage microcapsules. Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules were soaked in a 5wt% CaCl2 solution for 10 minutes, taken out and washed with ethanol 5 times to obtain a cycle of thermal conductivity enhanced phase change energy storage microcapsules. After the above steps were cycled 5 times and dried in a 50°C oven for 36 hours, thermal conductivity enhanced phase change energy storage microcapsules with a wall thickness of 240-280μm were obtained.

[0105] Step 3: Prepare phase change energy storage cement-based composite material specimens.

[0106] After the wall thickness controllable thermal conductivity enhanced phase change energy storage microcapsules are placed in a 60°C oven and dried for 24 hours, 200 parts of silicate cement, 90 parts of water, and 15 parts of wall thickness controllable thermal conductivity enhanced phase change microcapsules are taken and mixed. The wall thickness controllable thermal conductivity enhanced phase change microcapsules are added to the mold in multiple batches and oscillated multiple times. The specific method is: first add 1 / 4 of the wall thickness controllable thermal conductivity enhanced phase change microcapsules, then add 1 / 4 of the mold height cement slurry, oscillate for 30 seconds, then add 3 / 4 of the wall thickness controllable thermal conductivity enhanced phase change microcapsules and 1 / 2 of the mold height cement slurry in turn, oscillate for 30 seconds, and finally add the remaining cement slurry to the mold to prepare a phase change energy storage cement-based composite material specimen.

[0107] Example 4

[0108] While keeping other parameters unchanged, only the flow rates of the inner and outer phases in Example 1 were set to 500 μL / min and 1200 μL / min respectively, and thermally conductive enhanced phase change energy storage microcapsules with a particle size of 3000-3300 μm were prepared according to step 1 in Example 1.

[0109] The conditions of step 2 in Example 1 were kept unchanged to prepare thermally conductive enhanced phase change energy storage microcapsules with a wall thickness of 160-200 μm after three self-assembly cycles.

[0110] Example 5

[0111] While keeping other parameters unchanged, only the mass fraction of graphene in Comparative Example 2 was increased to 0.3%, and thermally conductive enhanced phase change energy storage microcapsules with a particle size of 3000-3300 μm were prepared according to step 1 in Example 1.

[0112] The conditions of step 2 were kept unchanged to prepare thermally conductive enhanced phase change energy storage microcapsules with a wall thickness of 160-200 μm after three self-assembly cycles.

[0113] Example 6

[0114] While keeping other parameters unchanged, only the mass fraction of graphene in Comparative Example 2 was increased to 0.5%, and thermally conductive enhanced phase change energy storage microcapsules with a particle size of 3000-3300 μm were prepared according to step 1 in Example 1.

[0115] The conditions of step 2 were kept unchanged to prepare thermally conductive enhanced phase change energy storage microcapsules with a wall thickness of 160-200 μm after three self-assembly cycles.

[0116] Example 7

[0117] While ensuring that the number of cycles in step 2 in comparative examples 2 and 3 is changed to 4 and 5 times respectively, and other materials and parameters remain unchanged, thermally conductive enhanced phase change energy storage microcapsules with wall thicknesses in the range of 200-240 μm and 240-280 μm are obtained.

[0118] Comparative Example 1

[0119] Weigh 9.4g of Span 80 as an emulsifier, pour into 375ml of molten phase-change paraffin with a melting point of 24℃, keep at 60℃, stir with a magnetic stirrer at 1300r / min for 20min, then add the solution to 1500ml of 3% sodium alginate solution, stir with a high-speed homogenizer at 6000r / min for 10min to form a stable water-in-oil emulsion. Pour the prepared emulsion into 3000ml of 2% CaCl2 solution, stir at 50℃ with a magnetic stirrer at 500r / min for 3min, centrifuge after polymerization, and obtain phase-change energy storage microcapsules, and wash with ethanol twice to remove unencapsulated paraffin. Finally, dry in a 50℃ oven for 36h, and wait until the phase-change energy storage microcapsules prepared by emulsion polymerization are obtained.

[0120] By comparison, it was found that the microcapsules prepared by emulsion polymerization generally showed agglomeration phenomenon, with particle sizes ranging from 1000μm to 10mm, uneven particle sizes and poor dispersibility.

[0121] Table 1 is a performance comparison table of phase change microcapsules prepared in various examples

[0122]

[0123] It can be seen from Table 1 that when the flow rate ratio remains unchanged, the particle size prepared by microfluidic technology is relatively uniform. When the internal and external flow rate ratio increases, the particle size of the prepared microcapsules will also increase; when other parameters remain unchanged, the thermal conductivity of the microcapsules increases with the increase in the proportion of thermal conductive materials. When the number of self-assembly cycles increases, the thermal conductivity of the microcapsules is slightly affected.

[0124] Table 2 shows the rupture rate of each example phase change microcapsule (after self-assembly) at room temperature

[0125] Microcapsule preparation example Particle size (before self-assembly) Wall thickness after self-assembly Rupture rate% Example 1 2000-2400μm 160-200μm 23 Example 2 2700-3000μm 200-240μm 15 Example 3 3000-3200μm 240-280μm 9 Example 4 3000-3300μm 160-200μm 22 Example 5 3000-3300μm 160-200μm 23 Example 6 3000-3300μm 160-200μm 21 Example 7 (cycle 4 times) 3000-3300μm 200-240μm 17 Example 7 (cycle 5 times) 3000-3300μm 240-280μm 12 Comparative Example 1 1000μm-10mm — 72

[0126] It can be seen from Table 2 that as the number of self-assembly cycles increases, the wall thickness of the microcapsules increases, while the rupture rate of the microcapsules decreases. At the same time, compared with the microcapsules prepared by the traditional emulsion polymerization method in Comparative Example 1, the rupture rate is significantly reduced.

[0127] The thermal conductivity enhanced phase change energy storage microcapsules prepared in the examples were used to prepare phase change energy storage cement-based composite material specimens according to step 3 in examples 1, 2 and 3, respectively.

[0128] Through the thermal regulation experiment, it was found that as the proportion of thermally conductive enhanced phase change energy storage microcapsules increased, when the temperature of the specimen was within the phase change temperature range, there would be an obvious temperature control effect. When the proportion of graphene was 0.5%, the mass fraction of sodium alginate solution was 5%, the mass fraction of CaCl2 solution was 5%, and the cement-based material ratio was as shown in Example 3, the thermal regulation ability of the specimen was the best, and the temperature control effect could reach ±4°C.

[0129] The above is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a cement-based composite material, characterized in that: The steps include: Step 1: Preparation of thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size The phase change energy storage material in a molten state is mixed evenly with the heat conductive material to form an inner phase solution; the sodium alginate aqueous solution is mixed evenly with the surfactant to form an outer phase solution; The inner phase solution and the outer phase solution are injected into the microfluidic chip to form water-in-oil microdroplets at the outlet of the microfluidic chip, and the microdroplets are poured into the receiving liquid with the assistance of gravity, and finally the thermal conductivity enhanced phase change energy storage microcapsules with uniform and controllable particle size are formed; Step 2: Preparation of thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness The thermally conductive enhanced phase-change energy storage microcapsules with uniform and controllable particle size prepared in step 1 are self-assembled layer by layer to obtain thermally conductive enhanced phase-change energy storage microcapsules with controllable wall thickness; Step 3: Preparation of phase change energy storage cement-based composite material specimens The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness obtained in step 2 are mixed with cement slurry, shaken multiple times, and solidified to obtain a phase change energy storage cement-based composite material specimen.

2. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step 1, the preparation method of the inner phase solution is: at a temperature of 50 to 70° C., directly adding the thermal conductive material into the phase change energy storage material in a molten state and stirring, continuously stirring for 1 to 2 hours, and performing ultrasonic oscillation for 1 to 3 hours; Preferably, the phase change energy storage material is a paraffin phase change material; Preferably, the paraffin phase change material includes at least one of n-tetradecane, n-hexadecane, n-octadecane and n-eicosane; Preferably, the thermally conductive material is a carbon-based material, and the carbon-based material is preferably at least one of graphite, graphene, graphene oxide, carbon nanotubes and carbon quantum dots; Preferably, the concentration of the thermally conductive material in the inner phase solution is 0.1-0.5 wt %.

3. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step 1, the external phase solution is prepared by mixing water, sodium alginate and a surfactant at a temperature of 50 to 70° C. and stirring at a speed of 800 to 1000 r / min for 40 to 60 min; Preferably, the surfactant is at least one of polysorbate 80, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl pyrrolidone; Preferably, the concentration of sodium alginate in the external phase solution is 3-5 wt %; the concentration of surfactant in the external phase solution is 0.5-1 wt %.

4. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step 1, the inner phase solution and the outer phase solution are injected into the microfluidic chip through a syringe pump, and the flow rate ratio of the inner phase solution to the outer phase solution is controlled; Preferably, the flow rate ratio of the inner phase solution to the outer phase solution is 1 / 4-1 / 2; Preferably, the receiving liquid is a CaCl2 solution with a mass fraction of 2 to 5 wt%; Preferably, the microfluidic chip is suspended vertically along the outlet direction; Preferably, the distance between the outlet end of the microfluidic chip and the liquid surface of the receiving liquid is 4 to 5 cm; Preferably, the inner diameter of the inner glass capillary of the microfluidic chip is 100 to 500 μm, and the outer diameter is 500 to 900 μm; Preferably, the inner diameter of the outer glass capillary of the microfluidic chip is 800-1200 μm, and the outer diameter is 1600-3000 μm.

5. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step 2, the layer-by-layer self-assembly is to immerse the thermally conductive enhanced phase change energy storage microcapsules with uniform and controllable particle size prepared in step 1 in a sodium alginate solution, and then wash them with ethanol to obtain pretreated thermally conductive enhanced phase change energy storage microcapsules; Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules were immersed in a CaCl2 solution, taken out and washed with ethanol, thus obtaining a cycle treatment; According to the above cycle, a thermally conductive enhanced phase change energy storage microcapsule with controllable wall thickness is obtained; Preferably, the layer-by-layer self-assembly is to immerse the thermally conductive enhanced phase-change energy storage microcapsules with uniform and controllable particle size prepared in step 1 in a sodium alginate solution with a mass fraction of 3-5wt% for 5-10 minutes, and then wash them with ethanol for 3-5 times to obtain pretreated thermally conductive enhanced phase-change energy storage microcapsules; Subsequently, the pretreated thermal conductivity enhanced phase change energy storage microcapsules are immersed in a CaCl2 solution with a mass fraction of 2 to 5 wt% for 5 to 10 minutes, taken out and washed with ethanol for 3 to 5 times to obtain a cycle-treated thermal conductivity enhanced phase change energy storage microcapsules; According to the above cycle, thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are obtained.

6. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step 2, the particle size of the prepared thermally conductive enhanced phase-change energy storage microcapsules with controllable wall thickness is controllable in the range of 1500 to 3500 μm, and the wall thickness is controllable in the range of 100 to 1000 μm.

7. A method for preparing a cement-based composite material according to claim 1, characterized in that: Step three is as follows: The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness obtained in step 2 are placed in a 40-60° C. oven and dried for 24-48 hours. The thermally conductive enhanced phase change energy storage microcapsules with controllable wall thickness are then mixed, stirred, and cured with cement slurry to obtain a phase change energy storage cement-based composite material specimen.

8. A method for preparing a cement-based composite material according to claim 1, characterized in that: In step three, the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are added multiple times. Preferably, 1 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness are added first, and then 1 / 4 of the mold height of cement and water formed by cement slurry is added, and oscillated for 20 to 30 seconds, and then 3 / 4 of the thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness and 1 / 2 of the mold height of cement slurry are added in turn, and oscillated for 20 to 30 seconds, and finally the remaining cement slurry is added to the mold.

9. A cement-based composite material, characterized in that: The cement-based composite material is prepared by the preparation method of any one of claims 1 to 8.

10. A cement-based composite material according to claim 9, characterized in that: Calculated by weight, it includes: 100-200 parts of cement, 45-90 parts of water, and 10-15 parts of thermal conductivity enhanced phase change energy storage microcapsules with controllable wall thickness.

Citation Information

Patent Citations

  • Composition for heat-storage material, and heat-storage material

    CN102666775A

  • Systems, structures and materials for electronic device cooling

    CN105050805A

  • Illuminated glass panel of a motor vehicle and motor vehicle having such a glass panel

    CN106794747A

  • Aerogel laminate and thermal insulation material

    CN107206736A

  • Self-repairing concrete and preparation method thereof

    CN110240457A

Cited By

  • A cement-based support for geothermal well fracturing fractures and a preparation method thereof

    CN122748993A